Evaluation of Willpower Training in Early Childhood in the Context of Value Acquisition - Handan Yalvaç Arıcı (Artuklu Akademi)

(untitled)
Will education, encompasses skills such as making decisions in line with one's desires and goals, taking responsibility, and managing motivation. This education significantly contributes to the development of various skills in children, including self-confidence, sense of responsibility, problem-solving, and communication. One of the negative consequences of digitization today is that children struggle to control themselves, which also complicates the acquisition of values. The study aims to reveal the effects of willpower education in early childhood on value acquisition. The study was conducted within the framework of a qualitative research design, and the document review technique was used in the data collection process. For this purpose, academic sources such as articles, books, and theses were examined, and data obtained from the existing literature were analyzed. After explaining the concepts of will and willpower education, the importance of willpower education in early childhood and its impact on children's value acquisition were evaluated. As a result of the study, the importance of willpower education in value acquisition is emphasized, and activities such as games and drama are recommended for value acquisition through willpower education.